2020
DOI: 10.1186/s40813-020-00158-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of the voluntary human approach test on commercial pig fattening farms: a meaningful tool?

Abstract: Background A Voluntary Human Approach Test (VHAT) was performed in pig pens, and relationships between environmental conditions and welfare indicators were investigated. Five variables were measured in 1668 pens in 214 fattening pig herds in Germany: time until the first contact (touching) between a pig and the person in the pen (TUFC), time until the observer was surrounded by pigs within a radius of approximately two meters, percentage of pigs relative to group size [%] surrounding the observer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…They often involve introducing a subject to an unfamiliar pig in order to observe social interactions between animals, dominance hierarchies, play behavior, and social recognition. A voluntary human approach test was conducted by Wegner et al (2020), which revealed that pigs who approached a motionless human observer more quickly were more likely to engage in forceful means of contact, i.e., biting, when compared to pigs who were more reserved [ 46 ]. Aggression tests assess aggressive behavior and response to social challenges in pigs.…”
Section: Reviewmentioning
confidence: 99%
“…They often involve introducing a subject to an unfamiliar pig in order to observe social interactions between animals, dominance hierarchies, play behavior, and social recognition. A voluntary human approach test was conducted by Wegner et al (2020), which revealed that pigs who approached a motionless human observer more quickly were more likely to engage in forceful means of contact, i.e., biting, when compared to pigs who were more reserved [ 46 ]. Aggression tests assess aggressive behavior and response to social challenges in pigs.…”
Section: Reviewmentioning
confidence: 99%
“…Another testing methodology that is often used in combination with the OFT is the human approach test (HAT), in which the pig is free to contact a motionless observer within the arena. The HAT evaluates the human-animal relationship based on the pig's possible fear reactions [ 22 ]. The latency to approach the observer [ 23 ] and the duration of contact are also recorded [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latency to approach the observer [ 23 ] and the duration of contact are also recorded [ 11 ]. This test is usually conducted on individual pigs rather than groups of pigs and has the advantage of low inter-observer variation [ 22 ]. Like the OFT and NOT, the HAT is also influenced by several factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation